Pengaruh Media Terhadap Pemerintahan dan Politik Masa Orde Baru dan Pasca Reformasi - Bakri, Zainal (At-Tabayyuun: Journal Islamic Studies, 2019)
Some theories describe how powerful and influential media in the life of society and the state. In developed countries whose governments to be democratic, the media and even positioned as the fourth pillar of democracy (the fourt estate). But it turns out in certain circumstances of a country, the media can also be fully controlled object and should follow the wishes of the ruler. The media in Indonesia is one of the bad experience in the history of his way when this country under the rule of the New Order regime. Controlling and controlled to be two things that run contradictory. On the one hand, the media should carry out social functions, including overseeing the policies taken by the government. But on the other hand, the media are also shackled by the government to harness the power of the instrument, to curb the grip even in the media so as not free expression and speech. Gait media against the government and politics in the new order after the reform and thus contrasts. At the new order shackled media, but later in the reform era, so free media and free from state intervention.